2019
DOI: 10.1371/journal.pone.0213746
|View full text |Cite
|
Sign up to set email alerts
|

Discoveries beyond BRCA1/2: Multigene testing in an Asian multi-ethnic cohort suspected of hereditary breast cancer syndrome in the real world

Abstract: BackgroundDue to historically low uptake of genetic testing, the mutational spectrum of Asians with Hereditary Breast Cancer (HBC) is not well understood. This study sought to understand the incidence and spectrum of germline mutations in Asian patients with suspected HBC in a clinic setting.Methods1056 patients with suspected HBC were seen in our Cancer (CA) Genetics Clinic from 2000–2017, of which 460 underwent genetic testing.ResultsOf 460 probands tested, 93% were female, 61% Chinese, 90% had prior CA, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…One of the seven mentioned families is from Argentina [15][16]. It was also reported in two sisters with ovarian cancer at 39 and 57 years old from other Chinese family (17]. The BRCA1 variant of our patient was located outside the region bounded by positions c.2282 to c.4071 which is associated with a significantly higher breast cancer risk compared with mutations inside the region [1].…”
Section: Discussionsupporting
confidence: 62%
“…One of the seven mentioned families is from Argentina [15][16]. It was also reported in two sisters with ovarian cancer at 39 and 57 years old from other Chinese family (17]. The BRCA1 variant of our patient was located outside the region bounded by positions c.2282 to c.4071 which is associated with a significantly higher breast cancer risk compared with mutations inside the region [1].…”
Section: Discussionsupporting
confidence: 62%
“…However, only a few studies to date report the prevalence of non- BRCA genes in the Chinese population. Samuel Guan Wei Ow et al analyzed 419 Asian patients suspected to have hereditary breast cancer syndrome who underwent genetic testing and found that the frequency of detrimental mutations in non- BRCA genes varied from 0 to 13.3% due to differences in ethnicity ( Ow et al, 2019 ). Using a 40 gene panel, another study found a non- BRCA gene mutation rate of 6.8% in a cohort of 937 Chinese breast cancer patients, with TP53 (1.9%), PALB2 (1.2%), CHEK2 (0.6%) and ATM (0.6%) being the major non- BRCA genes identified ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important in a multiethnic population like Singapore, where there are often limited allelic frequency data available in the public domain for variant classification (37)(38)(39). Genetic data is lacking for much of Singapore's diverse Asian population and this results in a higher rate of VUS (40,41). Due to these limitations, all genetic test reports are discussed at a weekly family review meeting, where the genetics team reviews every report and ensure the correct interpretation of all variants, paying attention to the population source of the reported allelic frequencies.…”
Section: Access-referral Source and Costsmentioning
confidence: 99%